BIOLOGICAL EFFECT OF SOME PLANT's SEED POWDERS AND ITS CONCENTRATIONS ON KHAPRA BEETLE Trogoderma granarium (Everts) . - Nashwa A. Sulieman (Mesopotamia Journal of Agriculture)
The results of the effect of some seed powders of Cuminum cyminum, Coriandrum sativum and Eniculum vulgre on some biological aspect of Trogoderma granarium showed a various repellancy and attractivness effects on larvae and adults of khapra beetle and the seed powder of C. cyminum exhibit a higher repellancy effects on the larvae and adults reached 42.5, 32.5% respectively, while the seed powder of C. sativum revealed a good attraction effect to the adults of khapra at a 6% concentration reached 60%. The results also showed that the seed powder of C. sativum Has a good effect in reducing the weight loss of Wheat grain at 8% concentration in comparison with the control. The seed powders of the tested plants exhibited different effects on insect rate of increase and sex ration of males and females.